Flexible Electronics: Solution‐Processed, Photo‐Patternable Fluorinated Sol–Gel Hybrid Materials as a Bio‐Fluidic Barrier for Flexible Electronic Systems (Adv. Electron. Mater. 3/2020). (9th March 2020) - Lee, Injun; Kim, Yong Ho; Jang, Jinhyeong; Lee, Kwang‐Heum; Jang, Junho; Lim, Young‐Woo; Park, Sang‐Hee Ko; Park, Chan Beum; Lee, Wonryung; Bae, Byeong‐Soo
Abstract : Solution‐processed and photo‐patternable fluorinated sol‐gel hybrid materials are demonstrated as a bio‐fluidic barrier for flexible electronic systems by Wonryung Lee, Byeong‐Soo Bae, and co‐workers in article number 1901065 . Ultra‐thin and flexible solution‐processed metal oxide transistors with these 1‐µm‐thick barrier films exhibit good performance after 16 hours in a bio‐fluidic environment and no degradation of electrical properties after 1000 cycles of mechanical testing.